PENGARUH RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2021 - Yuliasari, Ratna; Nasution, R (STKIP PGRI Jombang, 2023)
This study aims to determine and test the effect of Return On Assest and Debt to Equity Ratio both partially and simultaneously on Share Price in insurance subsector companies listed on the Indonesia Stock Exchange for the period 2014– 2021.The population of this study includes all insurance companies listed on the Indonesia Stock Exchange for the period 2014 – 2021. The sample was determined by purposive sampling. The data analysis technique in this study is descriptive. Hypothesis testing uses multiple linear regression analysis models.The results showed that (1) Return On Assets (X1) did not have a significant effect on the Stock Price. This is indicated by the calculated t value < t of the table which is 1,214 < 2,014 and the significance value (sig) of 0.231 > 0.05. (2) Debt to Equity Ratio (X2) has a significant effect on the Share Price. This is indicated by the calculated t value > t of the table which is 2,461 > 2,014 and the significance value (sig) of 0.018 < 0.05. (3) Return On Assets (X1) and Debt to Equity Ratio (X2) simultaneously have a significant effect on the Stock Price. This is indicated by the calculated F value > F of the table which is 4,583 > 3,200 and the significance value (sig) of 0.015 < 0.05.